Stacionarios mažmeninės prekybos tinklo plėtra Vilniuje ir Vilniaus apskrityje 1861 - 1904 metais - Ambrulevičiūtė, Aelita (Lietuvos istorijos studijos, 2008)
From a local point of view, Vilnius city and its suburbs were chosen to analyze the stationary trading development process. Vilnius, a city that is the center of gubernatorial and general gubernatorial administration, became the biggest Russian imperial North-West Land retail trade center in the 19th century and therefore clearly shows the stationary retail trade net development and citizens’ needs changes in the Lithuanian and Byelorussian territories when industrial manufacture extended from the 19th century’s second half until the beginning of the 20th century. The organization of the trade net in Lithuania started at the same time as the industrialization process when the manufacture order changed and began intensive trade structure reorganization. In the first decades after the reforms, no trade structure changes were noticed, and the biggest part of stores was selling "traditional" goods. The network of daily local enterprises in Lithuania in the middle of the 19th century was thin. The dynamics of the number of trade centers in the gubernatorial administration and district towns, villages, and countryside were uneven. The biggest part of the enterprises was founded in Vilnius and in the surroundings of other big towns. There wasn’t growth of local enterprises in small towns and villages in the countryside near Vilnius. The weak development of the network during the period of the 1860s-1890s was conditioned by several reasons: in the first decades after the reforms, agriculture hadn’t been commercialized yet, people’s purchasing power was weak, and peasant farms just tried to satisfy in-house needs with minimal expenditures. The intensity of stationary trade net development can be noticed from the 1890s as industrial manufacture volumes started to grow and agricultural commercialization became more intensive; some manufacture specialization became clearer, and we could see a growth of citizens’ needs. As a result, industrial enterprises pointed out the permanent goods realization requirement. To cover these needs, more stationary trade enterprises were established: only for the period from 1888 to 1904, the number of trade enterprises increased four times. Though the number of trade enterprises increased, there was not a large number of users in Vilnius city, and in the Vilnius suburb settlements, small and average enterprises dominated. Their spread was determined by small capital domination in the trade structure and slow turnover in big enterprises. This shows that the home market formation had still not been finished.